Transferrin receptor-targeting property of pabinafusp alfa facilitates its uptake by various types of human brain-derived cells in vitro - Fukatsu, Tomoki; Morio, Hanae; Furihata, Tomomi; Sonoda, Hiroyuki (Frontiers in Drug Delivery, 2023)
Pabinafusp alfa, which is an anti-mucopolysaccharidosis II drug, consists of iduronate-2-sulfatase (IDS) genetically fused with an anti-transferrin receptor (TfR) antibody. While IDS is known to enter cells via mannose-6-phosphate receptor (M6PR)-mediated endocytosis, the anti-TfR antibody moiety of pabinafusp alfa is supposed to trigger the TfR-mediated transcytosis involved in its blood-brain barrier (BBB) penetration to deliver IDS into the brain, which thus makes it effective for treatment of brain symptoms of the disease. However, since these uptake processes remain unexamined in vitro, this study aims at elucidating how human brain cells manipulate these receptors to facilitate pabinafusp alfa uptake. The results of pabinafusp alfa uptake assays showed that the TfR played an primary role in its uptake by brain microvascular endothelial cells. The TfR contribution was also found in neuronal cells at levels comparable to M6PR. Interestingly, the predominant roles of TfR over M6PR in pabinafusp alfa uptake were also observed in astrocytes and pericytes. To summarize, our results support the TfR-targeting strategy of pabinafusp alfa for facilitating its BBB penetration while simultaneously identifying previously unnoticed TfR roles in its uptake into human neuronal and non-neuronal brain cells. These findings are certain to provide important insights into the mechanisms behind clinical actions of pabinafusp alfa.